Qualitative study informing the development and content validity of the HAND-Q: a modular patient-reported outcome measure for hand conditions. Issue 4 (5th April 2022) - Sierakowski, Kyra; Kaur, Manraj N; Sanchez, Kathleen; Bain, Gregory; Cano, Stefan J; Griffin, Philip; Klassen, Anne; Pusic, Andrea L; Lalonde, Don; Dean, Nicola R
Abstract : Objectives: The purpose of this study was to identify and understand the issues that are relevant to patients with hand conditions. The data were used to develop a patient-reported outcome measure (PROM) for adults with hand conditions (HAND-Q) and refine it with input from patients and clinician experts. Design: Semistructured qualitative interviews were used to understand what matters to patients. Cognitive debriefing was used to refine preliminary HAND-Q scales. Setting: Hand clinics in tertiary healthcare centres in Canada, Australia and USA. Participants: Eligible participants were English-speaking adults who had experienced hand surgery in the preceding 12 months and were at least 4 weeks post-hand surgery A total of 62 in-depth interviews (females, n=34; mean age=65 years) were conducted to develop an item pool and draft the HAND-Q scales. The preliminary scales were refined through cognitive debriefing interviews with 20 participants and feedback from 25 clinician experts. All interviews were audiorecorded, transcribed verbatim and coded using a line-by-line approach. Results: Qualitative data were organised into two top-level domains of health-related quality of life and satisfaction with treatment outcomes. The scales were refined iteratively, and the field-test version included 319 unique items and 20 independently functioning scales. Conclusions: The HAND-Q is a comprehensive PROM developed using extensive patient and clinician expert input, following established guidelines for PROM development and validation. In the next phase, the psychometric properties of the HAND-Q will be established in an international field test, following which the HAND-Q will be available for use in clinical research and practice .